Sealing layer material for water electrolysis hydrogen production electrolytic cell and preparation method of sealing layer material

By using polytetrafluoroethylene, modified carbon fiber, high-temperature resistant compounds and metal salts doped with fluorine and nitrogen in the sealing layer material of the hydrogen-forming cell in the water electrolytic hydrogen production cell, and using specific preparation methods, the existing sealing layer materials are easily corroded and aging in high-temperature and high-corrosion environments, and a significant improvement in sealing performance and service life is achieved.

CN119708729APending Publication Date: 2025-03-28NINGBO ZHONGKEKE INNOVATION ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411903330.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The sealing layer materials of existing water electrolytic hydrogen electrolytic cells are prone to corrosion, aging or physical damage in high temperature and high corrosion environments, resulting in a decrease in sealing performance and service life.

Method used

The sealing layer material is composed of polytetrafluoroethylene, modified carbon fibers, high-temperature resistant compounds doped with fluorine and nitrogen, and metal salts doped with fluorine and nitrogen. The sealing layer material with high mechanical strength, high temperature resistance, corrosion resistance and physical damage resistance is formed by specific preparation methods, including coupling agent treatment, heat treatment and hot pressing treatment.

Benefits of technology

It significantly improves the sealing performance and service life of the sealing layer, enhances its tolerance to high temperature, high pressure and corrosion environments, and extends the service life of the sealing layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708729A_ABST
    Figure CN119708729A_ABST
Patent Text Reader

Abstract

The invention provides a sealing layer material for a water electrolysis hydrogen production electrolytic bath and a preparation method of the sealing layer material. The sealing layer material comprises polytetrafluoroethylene, modified carbon fibers, a high-temperature-resistant compound doped with fluorine and nitrogen and metal salt doped with fluorine and nitrogen, the high-temperature-resistant compound comprises at least one of molybdenum disulfide, molybdenum trioxide, tungsten trioxide, tungsten disulfide, manganese dioxide, titanium dioxide, zirconium dioxide and niobium pentoxide, and the metal salt comprises at least one of barium sulfate, lead sulfate and calcium sulfate, so that the sealing performance of the sealing layer is improved, and the service life of the sealing layer is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sealing materials, and in particular to a sealing layer material for an electrolytic cell for producing hydrogen by water electrolysis and a preparation method thereof. Background Art

[0002] The electrolyzer is the core device of the water electrolysis hydrogen production system. The sealing layer is the main component of the electrolyzer seal. The quality of its sealing largely determines the quality of the electrolyzer chamber sealing and insulation performance, which directly affects the safety and reliability of the entire hydrogen production system. Therefore, research on high-performance sealing materials is of great significance to the water electrolysis hydrogen production process.

[0003] At present, gaskets or sealing rings are usually used as the sealing layer of the electrolyzer, and the gaskets or sealing rings are made of rubber or plastic materials. However, gaskets or sealing rings made of rubber or plastic materials may be corroded, aged or physically damaged under certain conditions, such as high temperature and highly corrosive environment, resulting in reduced sealing performance and service life, and cannot meet the performance requirements of the electrolyzer. Summary of the invention

[0004] In view of this, the present application provides a sealing layer material for a water electrolysis hydrogen production electrolyzer and a preparation method thereof, so as to improve the sealing performance and service life of the sealing layer.

[0005] The present application provides a sealing layer material for an electrolytic cell for producing hydrogen by water electrolysis, characterized in that it includes polytetrafluoroethylene, modified carbon fiber, a high-temperature resistant compound doped with fluorine and nitrogen, and a metal salt doped with fluorine and nitrogen, wherein the high-temperature resistant compound includes at least one of molybdenum disulfide, molybdenum trioxide, tungsten trioxide, tungsten disulfide, manganese dioxide, titanium dioxide, zirconium dioxide and niobium pentoxide, and the metal salt includes at least one of barium sulfate, lead sulfate and calcium sulfate.

[0006] In some embodiments, the mass ratio of polytetrafluoroethylene: modified carbon fiber: high temperature resistant compound doped with fluorine and nitrogen and metal salt doped with fluorine and nitrogen is (70-85): (10-20): (4-7): (2.5-5).

[0007] In some embodiments, the modified carbon fiber is a modified carbon fiber treated with a coupling agent.

[0008] The present application also provides a method for preparing a sealing layer material for a water electrolysis hydrogen production electrolyzer, characterized in that the method is used to prepare the sealing layer material as described above, comprising:

[0009] reacting a coupling agent solution with carbon fiber to form modified carbon fiber, wherein the coupling agent in the coupling agent solution comprises at least one of vinyl triethoxysilane, vinyl trimethoxysilane, isobutyl triethoxysilane, triisostearoyl isopropyl titanate and isopropyl tri(dioctyl pyrophosphate acyloxy) titanate;

[0010] Grinding and mixing the modified carbon fiber with polytetrafluoroethylene, a high temperature resistant compound doped with fluorine and nitrogen, and a metal salt doped with fluorine and nitrogen to form a first sealing layer material precursor, wherein the high temperature resistant compound includes at least one of molybdenum disulfide, molybdenum trioxide, tungsten trioxide, tungsten disulfide, manganese dioxide, titanium dioxide, zirconium dioxide and niobium pentoxide, and the metal salt includes at least one of barium sulfate, lead sulfate and calcium sulfate;

[0011] In a reducing atmosphere, performing a first heat treatment on the first sealing layer material precursor to form a second sealing layer material precursor;

[0012] The second sealing layer material precursor is subjected to heat pressing treatment to form a sealing layer material.

[0013] In some embodiments, reacting the coupling agent solution with the carbon fiber to form the modified carbon fiber includes:

[0014] dissolving a coupling agent in a solvent to form a coupling agent solution;

[0015] The coupling agent solution is mixed with the carbon fiber and allowed to stand and soak to form an intermediate solution;

[0016] performing a second heat treatment on the intermediate solution to form an intermediate;

[0017] The intermediate is subjected to a third heat treatment to obtain modified carbon fibers.

[0018] In some embodiments, the temperature of the second heat treatment is 60-120° C., and the time of the second heat treatment is 6-24 hours.

[0019] In some embodiments, the temperature of the third heat treatment is 80-160° C., and the time of the third heat treatment is 0.5-6 hours.

[0020] In some embodiments, the temperature of the first heat treatment is 250-500° C., the time of the first heat treatment is 0.5-4 hours, and the reducing atmosphere includes at least one of hydrogen, carbon monoxide, a hydrogen-argon mixture, and ammonia.

[0021] In some embodiments, after reacting the coupling agent solution with the carbon fiber to form the modified carbon fiber, before grinding and mixing the modified carbon fiber with polytetrafluoroethylene, the high temperature resistant compound doped with fluorine and nitrogen, and the metal salt doped with fluorine and nitrogen, the method further comprises:

[0022] dissolving a high temperature resistant compound and a metal salt in hydrofluoric acid and performing an acid treatment under heating in a water bath to form a preformed precursor;

[0023] The prefabricated precursor is subjected to a fourth heat treatment in an ammonia atmosphere to form a high temperature resistant compound doped with fluorine and nitrogen and a metal salt doped with fluorine and nitrogen.

[0024] In some embodiments, the water bath heating temperature is 60-90° C., the acid treatment time is 4-12 h, the fourth heat treatment temperature is 400-800° C., and the fourth heat treatment time is 1-6 h.

[0025] The present application provides a sealing layer material for a water electrolysis hydrogen production electrolyzer and a preparation method thereof, comprising polytetrafluoroethylene, modified carbon fiber, a high-temperature resistant compound doped with fluorine and nitrogen, and a metal salt doped with fluorine and nitrogen, wherein the high-temperature resistant compound comprises at least one of molybdenum disulfide, molybdenum trioxide, tungsten trioxide, tungsten disulfide, manganese dioxide, titanium dioxide, zirconium dioxide and niobium pentoxide, and the metal salt comprises at least one of barium sulfate, lead sulfate and calcium sulfate, so as to improve the sealing performance and service life of the sealing layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 It is a flow chart of a method for preparing a sealing layer material for a water electrolysis hydrogen production electrolyzer provided in the present application;

[0028] Figure 2 It is a schematic diagram of the structure of the electrolytic cell provided in this application. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present application are clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application. In the absence of conflict, the following embodiments and their technical features can be combined with each other.

[0030] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by a person skilled in the art to which this application belongs. The terms used herein are for the purpose of describing specific embodiments only and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more related listed items. The terms "connection", "electrical connection", and "electrical connection" used herein include any direct and indirect electrical or structural connection means. Therefore, if the text describes a first device coupled / connected / electrically connected to a second device, it means that the first device can be directly electrically / structurally connected to the second device, or indirectly electrically / structurally connected to the second device through other devices or connection means.

[0032] The present application provides a sealing layer material for an electrolytic cell for producing hydrogen by water electrolysis, comprising polytetrafluoroethylene, modified carbon fiber, a high-temperature resistant compound doped with fluorine and nitrogen, and a metal salt doped with fluorine and nitrogen, wherein the high-temperature resistant compound comprises at least one of molybdenum disulfide, molybdenum trioxide, tungsten trioxide, tungsten disulfide, manganese dioxide, titanium dioxide, zirconium dioxide and niobium pentoxide, and the metal salt comprises at least one of barium sulfate, lead sulfate and calcium sulfate, so as to improve the sealing performance and service life of the sealing layer.

[0033] In the present application, a sealing layer material is formed by adding modified carbon fibers, high-temperature resistant compounds doped with fluorine and nitrogen, and metal salts doped with fluorine and nitrogen to polytetrafluoroethylene, so that the mechanical strength and rigidity of the sealing layer can be improved by the modified carbon fibers, and the sealing layer can be prevented from being broken or deformed due to excessive stress. At the same time, a good interface bonding is formed between the modified carbon fibers and the polytetrafluoroethylene to improve the high-temperature resistance, high-pressure resistance, corrosion resistance, aging resistance and physical damage resistance of the sealing layer material, and increase the service life of the sealing layer; and filling PTFE with high-temperature resistant compounds doped with fluorine and nitrogen and metal salts doped with fluorine and nitrogen can improve the compression resilience and long-term creep resistance of the sealing layer, thereby further increasing the sealing performance and service life of the sealing layer, that is, the sealing layer material provided in the present application has good high-temperature resistance, high-pressure resistance, corrosion resistance, aging resistance and physical damage resistance, thereby improving the service life and sealing performance of the sealing layer.

[0034] The present application provides a sealing layer material for a water electrolysis hydrogen production electrolyzer, including polytetrafluoroethylene, modified carbon fiber, a high temperature resistant compound doped with fluorine and nitrogen, and a metal salt doped with fluorine and nitrogen, the high temperature resistant compound including at least one of molybdenum disulfide, molybdenum trioxide, tungsten trioxide, tungsten disulfide, manganese dioxide, titanium dioxide, zirconium dioxide and niobium pentoxide, and the metal salt including at least one of barium sulfate, lead sulfate and calcium sulfate, so as to improve the sealing performance and service life of the sealing layer. The high temperature resistant compound is an acid-resistant and high temperature resistant metal oxide or sulfide. The metal salt is an acid-resistant and high temperature resistant metal salt.

[0035] In the present application, a sealing layer material is formed by adding modified carbon fibers, high-temperature resistant compounds doped with fluorine and nitrogen, and metal salts doped with fluorine and nitrogen to polytetrafluoroethylene, so that the mechanical strength and rigidity of the sealing layer can be improved by the modified carbon fibers, and the sealing layer can be prevented from being broken or deformed due to excessive stress. At the same time, a good interface bonding is formed between the modified carbon fibers and the polytetrafluoroethylene to improve the high-temperature resistance, high-pressure resistance, corrosion resistance, aging resistance and physical damage resistance of the sealing layer material, and increase the service life of the sealing layer; and filling PTFE with high-temperature resistant compounds doped with fluorine and nitrogen and metal salts doped with fluorine and nitrogen can improve the compression resilience and long-term creep resistance of the sealing layer, thereby further increasing the sealing performance and service life of the sealing layer, that is, the sealing layer material provided in the present application has good high-temperature resistance, high-pressure resistance, corrosion resistance, aging resistance and physical damage resistance, thereby improving the service life and sealing performance of the sealing layer.

[0036] In one embodiment, the mass ratio of polytetrafluoroethylene: modified carbon fiber: high temperature resistant compound doped with fluorine and nitrogen and metal salt doped with fluorine and nitrogen is (70-85): (10-20): (4-7): (2.5-5). Specifically, the mass ratio of polytetrafluoroethylene: modified carbon fiber: high temperature resistant compound and metal salt can be 70: 10: 4: 2.5, 75: 12: 4.3: 2.7, 79.3: 15.7: 5.7: 3.1, 83.4: 18.4: 6.4: 4.2, 84.3: 19.4: 6.7: 4.85 or 85: 20: 7: 5, etc., further increasing the sealing performance and service life of the sealing layer, that is, the sealing layer material provided by the present application has good resistance to high temperature, high pressure, corrosion, aging and physical damage, thereby improving the service life and sealing performance of the sealing layer.

[0037] In one embodiment, the modified carbon fiber is a modified carbon fiber treated with a coupling agent, wherein the coupling agent includes at least one of vinyl triethoxysilane, vinyl trimethoxysilane, isobutyl triethoxysilane, triisostearoyl isopropyl titanate, and isopropyl tri(dioctyl pyrophosphate) titanate.

[0038] See also Figure 1 , Figure 1 The present application also provides a method for preparing a sealing layer material for a water electrolysis hydrogen production electrolyzer, which is used to prepare the sealing layer material provided by the present application, comprising:

[0039] S11. Reacting a coupling agent solution with carbon fiber to form modified carbon fiber, wherein the coupling agent in the coupling agent solution includes at least one of vinyl triethoxysilane, vinyl trimethoxysilane, isobutyl triethoxysilane, triisostearyl isopropyl titanate and isopropyl tri(dioctyl pyrophosphate) titanate.

[0040] In one embodiment, step S11 includes:

[0041] The coupling agent is dissolved in a solvent to form a coupling agent solution; then, the coupling agent solution is mixed with carbon fiber and allowed to stand and soak to form an intermediate solution; then, the intermediate solution is subjected to a second heat treatment to form an intermediate; then, the intermediate is subjected to a third heat treatment to obtain modified carbon fiber. Specifically, the coupling agent is dissolved in an organic solvent to form a coupling agent solution of a certain concentration; then, the carbon fiber is placed in the coupling agent solution and allowed to stand and soak for surface modification to form an intermediate solution; then, the intermediate solution is placed in a drying oven for drying, that is, a second heat treatment is performed to form an intermediate. The equipment for the second heat treatment is not limited to a drying oven, but may be other equipment, which is not limited here; then, the dried intermediate is placed in a tubular furnace for a third heat treatment to activate it and obtain modified carbon fiber. The equipment for the third heat treatment is not limited to a tubular furnace, but may be other equipment, which is not limited here.

[0042] In one embodiment, the soaking time is 1-4h, and the mass proportion of the coupling agent in the coupling agent solution is 1-10%. Specifically, the soaking time can be 1h, 1.2h, 1.3h, 2.4h, 2.6h, 3.1h, 3.8h or 4h, and the mass proportion of the coupling agent in the coupling agent solution can be 1%, 1.4%, 1.8%, 1.98%, 2.1%, 2.5%, 3.7%, 4.6%, 5.8%, 6.4%, 7.1%, 9.4% or 10%, etc. The soaking time is set within this range to ensure the contact time between the coupling agent and the carbon fiber surface and the sufficiency of the reaction. If the soaking time is too short, the coupling agent may not have enough time to react with the carbon fiber surface, resulting in incomplete surface modification; if the time is too long, the coupling agent may be excessively adsorbed, affecting the subsequent processing process.

[0043] In the present application, the mass proportion of the coupling agent in the coupling agent solution is set to 1-10% to avoid the coupling agent in the coupling agent solution having too low a concentration, which leads to less adsorption of the coupling agent on the carbon fiber, resulting in incomplete surface modification. At the same time, it is avoided that the coupling agent in the coupling agent solution has too high a concentration, which leads to excessive adsorption of the coupling agent, which affects the final performance of the sealing layer material during subsequent processing.

[0044] In one embodiment, the temperature of the second heat treatment is 60-120°C, and the time of the second heat treatment is 6-24h. Specifically, the temperature of the second heat treatment can be 60°C, 62°C, 68°C, 78°C, 94°C, 107°C, 112°C, 118°C or 120°C, and the time of the second heat treatment can be 6h, 6.7h, 7.9h, 9.1h, 10.5h, 14h, 18h, 20h, 23h or 24h, etc., to better remove excess solvent on the surface of the carbon fiber and in the coupling agent solution, and prevent solvent residue from affecting the subsequent heat treatment process. If the temperature is too low or the time is too short, the solvent cannot be completely evaporated, affecting the subsequent reaction; if the temperature is too high or the time is too long, the coupling agent may decompose or the carbon fiber surface may be damaged, thereby affecting the quality and uniformity of the sealing layer material.

[0045] In one embodiment, the temperature of the third heat treatment is 80-160°C, and the time of the third heat treatment is 0.5-6h. Specifically, the temperature of the third heat treatment can be 80°C, 84.4°C, 94°C, 107°C, 112°C, 118°C, 120°C, 134°C, 147°C, 158°C or 160°C, etc., and the time of the third heat treatment can be 0.5h, 0.9h, 1.3h, 2.4h, 3.7h, 4.6h, 5.1h, 5.8h or 6h, so as to promote the chemical reaction between the coupling agent molecules and the surface of the carbon fiber, form a more stable chemical bond (such as a silicon oxygen bond, a titanium oxygen bond, etc.), ensure that the coupling agent can be fully activated and firmly combined with the surface of the carbon fiber, thereby improving the surface affinity of the carbon fiber and the binding force with the matrix material.

[0046] In the present application, the temperature of the third heat treatment activation is set to be higher than the temperature of the second heat treatment to promote further reaction of the coupling agent and ensure that the coupling agent is firmly bonded to the carbon fiber surface. This temperature difference helps the coupling agent to form chemical bonds and improve its adhesion and stability.

[0047] In one embodiment, after step S11, the method further includes:

[0048] After reacting the coupling agent solution with the carbon fiber to form the modified carbon fiber, before grinding and mixing the modified carbon fiber with polytetrafluoroethylene, the high temperature resistant compound doped with fluorine and nitrogen, and the metal salt doped with fluorine and nitrogen, the method further comprises:

[0049] The high temperature resistant compound and the metal salt are dissolved in hydrofluoric acid and subjected to acid treatment under water bath heating to form a prefabricated precursor; then, the prefabricated precursor is subjected to a fourth heat treatment under an ammonia atmosphere to form a high temperature resistant compound doped with fluorine and nitrogen and a metal salt doped with fluorine and nitrogen. Specifically, the high temperature resistant compound and the metal salt are placed in hydrofluoric acid and heated in a water bath for a period of time to form a prefabricated precursor doped with fluorine; then, after suction filtration and drying, they are placed in a tubular furnace and subjected to a fourth heat treatment under an ammonia atmosphere to obtain a high temperature resistant compound doped with fluorine and nitrogen and a metal salt doped with fluorine and nitrogen.

[0050] In one embodiment, the temperature of the water bath heating is 60-90°C, the time of the acid treatment is 4-12h, the temperature of the fourth heat treatment is 400-800°C, and the time of the fourth heat treatment is 1-6h. Specifically, the temperature of the water bath heating can be 60°C, 61°C, 62°C, 68°C, 78°C, 84°C, 89°C or 90°C, the time of the acid treatment can be 4h, 4.5h, 5h, 6h, 8h, 7.9h, 9.1h, 10.5h, or 11h or -12h, the temperature of the fourth heat treatment is 400-800°C, and the time of the fourth heat treatment can be 1h, 2.4h, 4h, 4.5h, 5h or 6h.

[0051] In one embodiment, the concentration of hydrofluoric acid is 0.5-5 mol / L. Specifically, the concentration of hydrofluoric acid can be 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2.4 mol / L, 3.1 mol / L, 4.7 mol / L or 5 mol / L.

[0052] S12. Grind and mix the modified carbon fiber with polytetrafluoroethylene, a high-temperature resistant compound doped with fluorine and nitrogen, and a metal salt doped with fluorine and nitrogen to form a first sealing layer material precursor, the high-temperature resistant compound includes at least one of molybdenum disulfide, molybdenum trioxide, tungsten trioxide, tungsten disulfide, manganese dioxide, titanium dioxide, zirconium dioxide and niobium pentoxide, and the metal salt includes at least one of barium sulfate, lead sulfate and calcium sulfate.

[0053] Specifically, the modified carbon fiber is cut into particles, and placed in a ball mill together with a high temperature resistant compound doped with fluorine and nitrogen, a metal salt doped with fluorine and nitrogen, and polytetrafluoroethylene (PTFE) particles according to a determined ratio, and fully ball milled and mixed on a planetary ball mill to obtain a first sealing layer material precursor. It should be noted that the grinding equipment is a planetary ball mill, and it can also be other grinding equipment, which is not limited here.

[0054] In the present application, the modified carbon fiber is cut and crushed into particles of the size of PTFE, and then the two are put into a ball mill together with a high-temperature resistant compound doped with fluorine and nitrogen and a metal salt doped with fluorine and nitrogen for ball milling to obtain a micro-nano level first sealing layer material precursor.

[0055] In the present application, the added modified carbon fiber particles, PTFE particles, high-temperature resistant compounds doped with fluorine and nitrogen, and metal salts doped with fluorine and nitrogen are first dried and then mixed and ball-milled to ensure the accuracy of the amount of material put into the grinding device. At the same time, moisture is avoided during the ball milling process to cause the materials to stick, affecting the ball milling efficiency and the inability to mix evenly between the materials, affecting the uniformity and quality of the formed sealing layer material.

[0056] In one embodiment, the rotation speed of grinding and mixing is 800-1300r / min, and the time of grinding and mixing is 8-16h. Specifically, the rotation speed of grinding and mixing can be 800r / min, 840r / min, 870r / min, 910r / min, 960r / min, 1001r / min, 1200r / min, 1280r / min or 1300r / min, etc., and the time of grinding and mixing can be 8h, 7.9h, 9.1h, 10.5h, 14h, 15.8h or 16h, etc. The time and rotation speed of grinding and mixing are set within this range to further improve the ball milling efficiency, while ensuring uniform mixing between materials, thereby ensuring the uniformity and quality of the sealing layer material.

[0057] S13. In a reducing atmosphere, performing a first heat treatment on the first sealing layer material precursor to form a second sealing layer material precursor.

[0058] Specifically, the micro-nano level first sealing layer material precursor obtained by ball milling is subjected to a first heat treatment under a reducing gas, so that the high-temperature resistant compounds doped with fluorine and nitrogen and the metal salt particles doped with fluorine and nitrogen spontaneously and orderly fill the gaps between the PTFE under the high-temperature reducing atmosphere, forming a second sealing layer material precursor with an ordered microstructure.

[0059] In the present application, the first sealing layer material precursor is subjected to a first heat treatment so that the sealing layer material formed subsequently has better uniformity.

[0060] In one embodiment, the temperature of the first heat treatment is 250-500°C, the first heat treatment time is 0.5-4h, and the reducing atmosphere includes at least one of hydrogen, carbon monoxide, hydrogen-argon mixed gas and ammonia. Specifically, the temperature of the first heat treatment can be 250°C, 259°C, 289°C, 300°C, 350°C, 380°C, 420°C, 480°C, 497°C or 500°C, etc., and the first heat treatment time can be 0.5h, 0.9h, 1.3h, 2.4h, 3.7h or 4h. The first heat treatment is carried out in a reducing atmosphere, and the temperature and time of the first heat treatment are set within this range so that the apparent structure of the formed second sealing layer material precursor has better uniformity, thereby improving the quality and uniformity of the sealing layer material.

[0061] S14, performing heat pressing treatment on the second sealing layer material precursor to form a sealing layer material.

[0062] Specifically, the second sealing layer material precursor is placed in a mold, and hot pressing is performed multiple times according to program parameters set by a hot press machine to obtain the sealing layer material.

[0063] Furthermore, the precursor powder of the second sealing layer material is placed in a mold, first shaped at a relatively low temperature, and then hot-pressed for multiple times using a hot press to obtain the final modified composite PTFE sealing layer material.

[0064] Furthermore, after the second sealing layer material precursor powder is placed in the mold for shaping, the hot pressing temperature is gradually increased, and hot pressing is performed multiple times to form the sealing layer material, so as to avoid sintering of the second sealing layer material precursor powder due to the initial hot pressing temperature being too high, thereby affecting the performance of the sealing layer.

[0065] In one embodiment, the temperature of the hot pressing treatment is 60-300°C, the pressure of the hot pressing treatment is 3-20MPa, and the time of the hot pressing treatment is 5-60min. Specifically, the temperature of the hot pressing treatment can be 60°C, 70°C, 80°C, 84.4°C, 94°C, 107°C, 112°C, 118°C, 120°C, 134°C, 147°C, 158°C, 160°C, 200°C, 250°C, 289°C or 300°C, etc., the pressure of the hot pressing treatment can be 3MPa, 4.5MPa, 5.8MPa, 8.9MPa, 15.1MPa, 17.4MPa, 19.8MPa or 20MPa, etc., and the time of the hot pressing treatment can be 5min, 6.8min, 10.4min, 18.7min, 20.7min, 37.4min, 45min, 56min, 58min or 60min, etc.

[0066] In the present application, a high temperature resistant compound doped with fluorine and nitrogen and a metal salt doped with fluorine and nitrogen are filled while the modified carbon fiber is compounded with PTFE, so as to obtain a sealing layer material for a water electrolysis hydrogen production electrolyzer having excellent high temperature resistance, high pressure resistance, corrosion resistance, aging resistance and physical damage resistance, long service life and excellent sealing performance. At the same time, the preparation method provided in the present application has a concise and clear preparation process, simple operation, easy mass preparation, easy promotion and use, and good economic value.

[0067] See also Figure 2 , Figure 2 : is a schematic diagram of the structure of the electrolytic cell provided in the present application. The structure of the electrolytic cell 10 includes a membrane electrode 100, an anode 200, a cathode 300, a bipolar plate 400, a sealing layer 500 and an end plate 600, wherein the anode 200 and the cathode 300 are respectively located on both sides of the membrane electrode 100, and the sealing layer 500, the bipolar plate 400, the sealing layer 500 and the end plate 600 are sequentially arranged on the side of the anode 200 facing away from the membrane electrode 100 and the side of the cathode 300 facing away from the membrane electrode 100, and the sealing layer 500 is the sealing layer 500 provided in the present application.

[0068] In the present application, the use of the sealing material provided in the present application can improve the compression resilience and long-term creep resistance of the sealing layer, thereby further increasing the sealing performance and service life of the sealing layer. That is, the sealing layer material provided in the present application has good resistance to high temperature, high pressure, corrosion, aging and physical damage, thereby improving the service life and sealing performance of the sealing layer.

[0069] Example 1

[0070] 877g of vinyltrimethoxysilane was dissolved in 10L of ethanol to prepare a coupling agent solution with a mass concentration of 10%; then, 200g of carbon fiber was completely immersed in the prepared coupling agent solution for 2 hours to obtain an intermediate solution; then, the intermediate solution was placed in a 70°C drying oven for 12 hours, that is, a second heat treatment was performed, and after drying, an intermediate was obtained; then, the intermediate was placed in a quartz tube and placed in a tube furnace for heat treatment at 120°C for 1 hour, that is, a third heat treatment was performed to obtain the desired modified carbon fiber; then, 10 100g of barium sulfate and 100g of molybdenum disulfide were immersed in a 1mol / L hydrofluoric acid solution, and acid-treated in a 70°C water bath for 6 hours. After the acid treatment was completed, they were filtered, dried, and crushed to obtain fluorine-doped barium sulfate and molybdenum disulfide, that is, to obtain an intermediate; then, the crushed intermediate was placed in a quartz tube, placed in a tube furnace at 600°C in an ammonia atmosphere for a fourth heat treatment for 3 hours to obtain barium sulfate and molybdenum disulfide doped with fluorine and nitrogen; then, 200g of the modified carbon fiber was cut into PTFE particle size and mixed with 1600g of PTFE particles, 100g of barium sulfate doped with fluorine and nitrogen, and 100g of molybdenum disulfide doped with fluorine and nitrogen are mixed together and loaded into a ball mill, the ball mill is fixed on a planetary ball mill, the planetary ball mill speed is set to 1200r / min, the ball milling time is 12 hours, the planetary ball mill is turned on for ball milling, and after the ball milling is completed, the first sealing layer material precursor is obtained; then, the first sealing layer material precursor is placed in a quartz tube, placed in a tubular furnace in a hydrogen-argon mixed atmosphere at 300°C for 2 hours, that is, the first heat treatment is performed to obtain the activated second sealing layer material precursor. The second sealing layer material precursor is placed in a mold of a customized shape for compaction and shaping, and the hot pressing temperature is set to 90°C, the pressure is 5MPa, and the hot pressing time is 10 minutes, and the first step of hot pressing molding is performed. After the sealing layer material is initially formed, the hot pressing temperature is set to 240°C, the pressure is 14MPa, and the hot pressing time is 30 minutes, and the final hot pressing treatment is performed to obtain the desired sealing layer material.

[0071] Example 2

[0072] 620.13g of isopropyl triisostearyl titanate was dissolved in 15L of isopropanol to prepare a coupling agent solution with a mass concentration of 5%; then, 300g of carbon fiber was completely immersed in the prepared coupling agent solution for 4 hours to obtain an intermediate solution; then, the intermediate solution was placed in a 60°C drying oven and dried for 16 hours, that is, a second heat treatment was performed, and after drying, an intermediate was obtained; then, the intermediate carbon fiber was placed in a quartz tube and placed in a tube furnace for a third heat treatment at 100°C for 2.5 hours to obtain the desired modified carbon fiber; then, 64.29g of lead sulfate and 39.24g of tungsten disulfide were added. 78.61g of tungsten trioxide was immersed in a 0.5mol / L hydrofluoric acid solution, and acid-treated in a 60°C water bath for 4 hours. After the acid treatment was completed, it was filtered, dried, and crushed to obtain fluorine-doped lead sulfate, tungsten disulfide, and tungsten trioxide; then, the crushed fluorine-doped lead sulfate, tungsten disulfide, and tungsten trioxide were placed in a quartz tube, placed in a tube furnace at 700°C in an ammonia atmosphere for a fourth heat treatment for 4 hours to obtain fluorine- and nitrogen-doped lead sulfate, tungsten disulfide, and tungsten trioxide; then, 300g of the modified carbon fiber was cut into PTFE particle size and mixed with 1660.71g PTFE particles, 64.29g of lead sulfate doped with fluorine and nitrogen, 39.24g of tungsten disulfide doped with fluorine and nitrogen, and 78.61g of tungsten trioxide doped with fluorine and nitrogen are mixed evenly and loaded into a ball mill, and the ball mill is fixed on a planetary ball mill, and the planetary ball mill is set to rotate at 1300r / min and the ball milling time is 16 hours. The planetary ball mill is turned on for ball milling. After the ball milling is completed, a first sealing layer material precursor is obtained; then, the first sealing layer material precursor is placed in a quartz tube, placed in a tubular furnace, and subjected to a first heat treatment at 350°C for 3.5 hours under a carbon monoxide atmosphere to obtain an activated second sealing layer material precursor; then, the second sealing layer material precursor is placed in a mold of a customized shape for compaction and shaping, and the hot pressing temperature is set to 80°C, the pressure to 4.5MPa, and the hot pressing time to 10 minutes to perform the first hot pressing molding. After the sealing layer material is initially formed, the hot pressing temperature is set to 180°C, the pressure is 12 MPa, and the hot pressing time is 15 minutes for a second hot pressing molding; then, the hot pressing temperature is set to 250°C, the pressure is 18 MPa, and the hot pressing time is 25 minutes for a final hot pressing treatment to obtain the required sealing layer material.

[0073] Comparison Example

[0074] A conventional single-layer sealing material having the same size as that in the embodiment is prepared using PTFE.

[0075] The performance of the sealing layer materials of Example 1, Example 2 and the control example was tested:

[0076] (1) Vickers hardness test: The Vickers hardness was tested using a HV-112 or 114 Vickers hardness tester from Mitutoyo Precision Measuring Instruments Co., Ltd., Japan, with a scale of HV, a special diamond indenter (HM-211), a test force of 0.5 gf (4.903 N), a load time of T = 90 s, an objective lens of 10X, and a resolution of 0.1 μm.

[0077] (2) Compression rebound performance measurement: The compression rebound performance was tested using a WDW-200Y creep relaxation testing machine produced by Jinan Xinshijin Testing Machine Co., Ltd., with a preload of 1 MPa, a test load of 34.5 MPa, a force speed of 0.5 MPa / s, and a holding time of T = 60 s.

[0078] (3) Creep relaxation performance measurement: The constant stress creep and constant deformation relaxation performance were tested on a WDW-200Y creep relaxation testing machine with a test load of 45 MPa, a force speed of 0.5 MPa / s, and a holding time of T=600 s.

[0079] (4) Air tightness test: The sealing layer materials of the embodiment and the control example were placed in our company's water electrolysis hydrogen production electrolyzer and operated stably for 24 hours, and the gas leakage rate was detected.

[0080] The Vickers hardness of the sealing layer material in Example 1 is 3.7HV, the compression rate is 15.62%, the rebound rate is 55.98%, the creep rate is 27.14%, the relaxation rate is 25.44%, and the gas leakage rate is ≦1%. The Vickers hardness of the sealing layer material in Example 2 is 4.1HV, the compression rate is 12.51%, the rebound rate is 59.80%, the creep rate is 25.22%, the relaxation rate is 22.38%, and the gas leakage rate is ≦1%. The Vickers hardness of the sealing layer material in the control example is 3.3HV, the compression rate is 19.96%, the rebound rate is 47.81%, the creep rate is 31.83%, the relaxation rate is 29.16%, and the gas leakage rate is ≧5%. It can be seen from the above test data that the composite modified PTFE sealing layer material prepared by this method has better hardness, compression rebound performance, anti-creep relaxation ability and air tightness than the simple PTFE sealing layer material.

[0081] The above descriptions are merely embodiments of the present application and are not intended to limit the patent scope of the present application. Any equivalent structural or equivalent process transformations made using the contents of the specification and drawings of the present application, such as the mutual combination of technical features between the embodiments, or direct or indirect application in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A sealing layer material for a water electrolysis hydrogen production electrolyzer, characterized in that: It includes polytetrafluoroethylene, modified carbon fiber, a high-temperature resistant compound doped with fluorine and nitrogen, and a metal salt doped with fluorine and nitrogen, wherein the high-temperature resistant compound includes at least one of molybdenum disulfide, molybdenum trioxide, tungsten trioxide, tungsten disulfide, manganese dioxide, titanium dioxide, zirconium dioxide and niobium pentoxide, and the metal salt includes at least one of barium sulfate, lead sulfate and calcium sulfate.

2. The sealing layer material for the electrolytic cell for producing hydrogen by water electrolysis according to claim 1, characterized in that: The mass ratio of polytetrafluoroethylene: modified carbon fiber: high temperature resistant compound doped with fluorine and nitrogen and metal salt doped with fluorine and nitrogen is (70-85): (10-20): (4-7): (2.5-5).

3. The sealing layer material for the electrolytic cell for producing hydrogen by water electrolysis according to claim 1, characterized in that: The modified carbon fiber is a modified carbon fiber treated with a coupling agent.

4. A method for preparing a sealing layer material for an electrolytic cell for producing hydrogen by water electrolysis, characterized in that: The sealing layer material for preparing any one of claims 1 to 3 comprises: reacting a coupling agent solution with carbon fiber to form modified carbon fiber, wherein the coupling agent in the coupling agent solution comprises at least one of vinyl triethoxysilane, vinyl trimethoxysilane, isobutyl triethoxysilane, triisostearoyl isopropyl titanate and isopropyl tri(dioctyl pyrophosphate acyloxy) titanate; Grinding and mixing the modified carbon fiber with polytetrafluoroethylene, a high temperature resistant compound doped with fluorine and nitrogen, and a metal salt doped with fluorine and nitrogen to form a first sealing layer material precursor, wherein the high temperature resistant compound includes at least one of molybdenum disulfide, molybdenum trioxide, tungsten trioxide, tungsten disulfide, manganese dioxide, titanium dioxide, zirconium dioxide and niobium pentoxide, and the metal salt includes at least one of barium sulfate, lead sulfate and calcium sulfate; In a reducing atmosphere, performing a first heat treatment on the first sealing layer material precursor to form a second sealing layer material precursor; The second sealing layer material precursor is subjected to heat pressing treatment to form a sealing layer material.

5. The method for preparing a sealing layer material for an electrolytic cell for producing hydrogen by water electrolysis according to claim 4, characterized in that: In reacting the coupling agent solution with the carbon fiber to form the modified carbon fiber, the method includes: dissolving a coupling agent in a solvent to form a coupling agent solution; The coupling agent solution is mixed with the carbon fiber and allowed to stand and soak to form an intermediate solution; performing a second heat treatment on the intermediate solution to form an intermediate; The intermediate is subjected to a third heat treatment to obtain modified carbon fibers.

6. The method for preparing a sealing layer material for an electrolytic cell for producing hydrogen by water electrolysis according to claim 5, characterized in that: The temperature of the second heat treatment is 60-120° C., and the time of the second heat treatment is 6-24 hours.

7. The method for preparing a sealing layer material for an electrolytic cell for producing hydrogen by water electrolysis according to claim 5, characterized in that: The temperature of the third heat treatment is 80-160° C., and the time of the third heat treatment is 0.5-6 hours.

8. The method for preparing a sealing layer material for an electrolytic cell for producing hydrogen by water electrolysis according to claim 4, characterized in that: The temperature of the first heat treatment is 250-500° C., the time of the first heat treatment is 0.5-4 hours, and the reducing atmosphere includes at least one of hydrogen, carbon monoxide, a hydrogen-argon mixed gas and ammonia.

9. The method for preparing a sealing layer material for an electrolytic cell for producing hydrogen by water electrolysis according to claim 4, characterized in that: After reacting the coupling agent solution with the carbon fiber to form the modified carbon fiber, before grinding and mixing the modified carbon fiber with polytetrafluoroethylene, the high temperature resistant compound doped with fluorine and nitrogen, and the metal salt doped with fluorine and nitrogen, the method further comprises: The high temperature resistant compound and the metal salt are dissolved in hydrofluoric acid and subjected to acid treatment under heating in a water bath to form a preformed precursor; The prefabricated precursor is subjected to a fourth heat treatment in an ammonia atmosphere to form a high temperature resistant compound doped with fluorine and nitrogen and a metal salt doped with fluorine and nitrogen.

10. The method for preparing a sealing layer material for an electrolytic cell for producing hydrogen by water electrolysis according to claim 9, characterized in that: The temperature of the water bath heating is 60-90° C., the time of the acid treatment is 4-12 hours, the temperature of the fourth heat treatment is 400-800° C., and the time of the fourth heat treatment is 1-6 hours.